Asuhan Keperawatan Jiwa Pada Sdr. R Dengan Masalah Utama Isolasi Sosial: Menarik Diri Akibat Skizofrenia Tak Terinci Di Ruang Gatotkaca RSJD Dr. Amino Gondohutomo Provinsi Jawa Tengah - Lili Kusniawati; Titi Sri Suyanti (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Schizophrenia is a mental disorder characterized by deviation in attitudes, thoughts and behaviors, and can cause positive and negative symptoms. One of the most frequently occurring negative symptoms is social withdrawal, which leads to the problem of Social Isolation: Withdrawal. Social isolation is a condition that causes individuals to experience a decline or even inability to interact with others and their environment. The purpose of this case study was to apply nursing care to patients with social isolation: withdrawal due to undifferentiated schizophrenia in Gatotkaca Ward of RSJD dr. Amino Gondohutomo, Central Java Province. This scientific paper was written using a descriptive method in the form of a case study through the nursing process approach. Data collection methods used were interview, observation, documentation study, and literature study. Nursing diagnoses that emerged in the patient with Social Isolation: Withdrawal were Social Isolation as the Core Problem, Low Self-Esteem as the Cause, Risk of Hallucination as the Effect, and Self-Care Deficit as a concurrent problem. Interventions were only carried out on Social Isolation and Self-Care Deficit problems, consisting of SP 1 through SP 3 for Social Isolation and SP 2 for Self-Care Deficit: Grooming. After nursing implementation for 4 days, of the 4 nursing diagnoses that emerged, only 2 nursing diagnoses were intervened, namely Social Isolation and Self-Care Deficit. SP 1 through SP 3 for Social Isolation and SP2 for Self-Care Deficit: Grooming were competently achieved. This indicates that the goals of the Implementation Strategy provided were achieved cognitively, affectively, and psychomotorically.